Dampak Intellectual Capital dan Kinerja Lingkungan terhadap Nilai Perusahaan Perbankan di Indonesia: Studi Empiris pada Emiten BEI Tahun 2017–2021 - Dieviya; Nuraeni; M. Sulhan (Journal of Economic, Management and Entrepreneurship, 2024)
This research aims to examine and measure the influence of intellectual capital and environmental performance on company value. The research object includes banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2017–2021. The research sample was selected using purposive sampling techniques, with a total of 46 companies. Data analysis was carried out using the Partial Least Square (PLS) approach using WarpPLS software version 7.0. The results of the study show that: (1) Intellectual capital has a positive and significant effect on environmental performance, (2) Intellectual capital has a positive and significant effect on company value, and (3) environmental performance has a negative and significant effect on company value